Effect of umbelliferone (7-hydroxycoumarin, 7-HOC) on the enzymatic, edematogenic and necrotic activities of secretory phospholipase A2 (sPLA2) isolated from Crotalus durissus collilineatus venom - Toyama, D. O.; Marangoni, S.; Diz-Filho, E. B. S.; Oliveira, S. C. B.; Toyama, M. H. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
Flavonoids, coumarins and other polyphenolic compounds are powerful antioxiants both in hydrophilic and lipophylic environments with diverse pharmacological properties including anti-inflammatory activity. Despite being widely used as powerful therapeutic agents for blood coagulation disorders, more specifically to control some serine protease enzymes, the mechanism of anti-inflammatory activity of coumarins is unknown, unlike that of flavonoids. Although their controlling effect on serine proteases is well acknowledged, their action on secretory phospholipase A2 (sPLA2) remains obscure. The present study describes the interaction between umbelliferone (7-HOC) and the sPLA2 from Crotalus durissus collilineatus venom. In vitro inhibition of sPLA2 enzymatic activity by 7-HOC was estimated using 4N3OBA as substrate, resulting in an irreversible decrease in such activity proportional to 7-HOC concentration. The biophysical interaction between 7-HOC and sPLA2 was examined by fluorescent spectral analysis and circular dichroism studies. Results from both techniques clearly showed that 7-HOC strongly modified the secondary structure of this enzyme and CD spectra revealed that it strongly decreased sPLA2 alphahelical conformation. In addition, two-dimensional electrophoresis indicated an evident difference between HPLC-purified native and 7-HOC-treated sPLA2s, which were used in pharmacological experiments to compare their biological activities. In vivo anti-inflammatory activity was assessed by the sPLA2-induced mouse paw edema model, in which 7-HOC presented an effect similar to those of dexamethasone and cyproheptacline against the pro-inflammatory effect induced by native sPLA2 on the mouse paw edema, mast cell degranulation and skin edema. on the other hand, 7-HOC exhibited a more potent inhibitory effect on sPUL2 than that of p-bromophenacyl bromide (p-BPB). Our data suggest that 7-HOC interacts with sPLA2 and causes some structural modifications that lead to a sharp decrease or inhibition of the edematogenic and myotoxic activities of this enzyme, indicating its potential use to suppress inflammation induced by sPLA2 from the snake venom. (C) 2008 Published by Elsevier Ltd.
Keywords: Secretary phospholipase A2 (sPLA2); Umbelliferone (7-HOC); Snake venom; Anti-venom; Anti-inflammatory; Circular dichroism